Recruitment and retention strategies to promote research engagement among caregivers and their children: A scoping review - Tammy E. Corr; Alma Jusufagic; James Basting; Catherine Caldwell; Steven King; Aleksandra E. Zgierska (Journal of Clinical and Translational Science)
Long-term health and developmental impact after in utero opioid and other substance exposures is unclear. There is an urgent need for well-designed, prospective, long-term observational studies. The HEALthy Brain and Child Development Study aims to address this need. It will require optimizing recruitment and retention of caregivers and young children in long-term research. Therefore, a scoping review of original research articles, indexed in the PubMed database and published in English between January 1, 2010, and November 23, 2023, was conducted on recruitment and retention strategies of caregiver–child (≤6 years old) dyads in observational, cohort studies. Among 2,902 titles/abstracts reviewed, 37 articles were found eligible. Of those, 29 (78%) addressed recruitment, and 18 (49%) addressed retention. Thirty-four (92%) articles focused on strategies for facilitating recruitment and/or retention, while 18 (49%) described potentially harmful approaches. Recruitment and retention facilitators included face-to-face and regular contact, establishing a relationship with study personnel, use of technology and social platforms, minimizing inconveniences, and promoting incentives. This review demonstrates that numerous factors can affect engagement of caregivers and their children in long-term cohort studies. Better understanding of these factors can inform researchers about optimal approaches to recruitment and retention of caregiver–child dyads in longitudinal research.